Quadricuspid aortic valve diagnosed by transthoracic echocardiography in childhood - Akalin, Figen; Demirel, Banu; Urenden, Pinar; Biyikli, Neşe (The Turkish Journal of Pediatrics, 2010)
Quadricuspid aortic valve is a rare congenital malformation of the heart leading to significant aortic regurgitation or stenosis. Its diagnosis by transthoracic echocardiography is difficult. Most of the cases are diagnosed during surgery or autopsy. Associated abnormalities of the coronary arteries should also be searched, since surgical injury may have devastating results. We herein present an eight-year-old girl found to have a quadricuspid aortic valve during evaluation of chronic renal disease and systemic hypertension.